Conditional knockout of tissue factor pathway inhibitor 2 in vascular endothelial cells accelerates atherosclerotic plaque development in mice. (January 2016) - Hong, Jin; Liu, Rongle; Chen, Lewen; Wu, Bangwei; Yu, Jia; Gao, Wen; Pan, Junjie; Luo, Xinping; Shi, Haiming
Abstract: Background: Tissue factor pathway inhibitor-2 (TFPI-2) regulates matrix metalloproteinases activation and extracellular matrix degradation. Over-expression of TFPI-2 enhances atherosclerotic plaque stability. The aim of this study is to investigate the effect of conditional knockout (KO) of TFPI-2 in vascular endothelial cells on the initiation and development of atherosclerotic plaque. Methods: A Cre/mloxP conditional KO system and Tek-Cre mice were used to generate offsprings with monoallelic deletion of the TFPI-2 gene in endothelial cells. TFPI-2 fl/+ /Tek-Cre mice, TFPI-2 fl/+ mice and ApoE −/− mice (n = 6 for each group) were included. Arteries were obtained. HE, EVG and anti-α-SMA staining were used to examine the morphology of vessel and plaque. Protein expression and phosphorylation were detected by Western blot or immunohistochemistry. Results: TFPI-2 fl/+ /Tek-Cre mice were generated. TFPI-2 level decreased to 40.68% in TFPI-2 fl/+ /Tek-Cre group. TFPI-2 fl/+ /Tek-Cre developed plaques when no plaque was found in TFPI-2 fl/+ mice. Compared with ApoE −/− group, TFPI-2 fl/+ /Tek-Cre group has smaller plaque area, decreased lipid content and less buried fibrous cap layers. MMP-2 and MMP-9 in TFPI-2 fl/+ /Tek-Cre group was higher than in TFPI-2 fl/+  group. The phosphorylation of PPAR-α and PPAR-γ was decreased in TFPI-2 fl/+ /Tek-Cre group. Conclusions: A novel mouse model is presented and can be used to investigate the role of TFPI-2 in the process of atherosclerosis. Our findings suggest that monoallelic deletion of TFPI-2 gene in vascular endothelial cells leads to significant downregulation of TFPI-2. TFPI-2 deficiency may accelerate initiation of atherosclerotic lesion in mice. Elevated MMP-2 and 9 and decreased phosphorylation of PPAR-α and PPAR-γ may contribute to this phenotype. Highlights: A novel TFPI-2 fl/+ /Tek-Cre mouse model is presented. TFPI-2 deficiency may accelerate initiation of atherosclerotic lesion. Possible mechanism includes increased MMP-2 and 9, activated PPAR-α and γ.